Description of Nurse's Perception of Fulfillment the Rights of People with Mental Disorders: Literature Review - Marista Fiana; Shanti Wardaningsih (Universitas Aisyah Pringsewu, 2022)
Human rights are rights that are obtained by everyone, including people with mental disorders. One form of fulfillment of human rights is to obtain health services. Nurses are the spearhead of health services, including Those who work in mental hospitals need to have a high commitment to be able to provide optimal service to their patients, considering that the patient's condition requires special treatment. Nurses' perceptions of mental disorders in general need to be known to plan an appropriate program. To review the literature on nurses' perceptions of the fulfillment of the rights of people with mental disorders. Literature review using three databases, namely Pubmed, Google Scholar, and Proquest, using the keywords